Evaluation of Open Educational Resources for an Introductory Exercise Science Course - Hillman, Angela R.; Brooks, Anna R.; Barr, Marcus; Strycker, Jesse (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
While open educational resources (OER) have gained popularity, nearly three quarters of faculty are not aware they are available for use. However, when used, they are well received and do not negatively impact quality of learning. OER can be used within a variety of platforms, including software that aims to be more interactive and engage students in active learning and assessment. One such platform is Top Hat, which was used by the authors of this study to develop a textbook for an introductory exercise science course. We assessed student’s perceptions of Top Hat and barriers to use for reading their textbook and for class assessments over the course of two years. A total of 486 students were registered for this course. Although two thirds of students had previous experience with Top Hat and half of those used the textbook feature, students (n = 39, 38%) were apprehensive about reading their textbook online via Top Hat. However, these feelings resolved as students became comfortable with the platform’s features. Nearly 80% of students have sometimes or never acquired their textbooks before the start of the semester, despite 96% who expressed the importance of having their materials accessible online and available on or before the first day of the course. This indicated that students understood the importance of having their materials for the start of the semester, however they perceived the barriers of purchasing books to be greater. Therefore, using OER and Top Hat removed student learning barriers and had potential to increase course participation and success.